2018
DOI: 10.5397/cise.2018.21.3.127
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome after Arthroscopic Capsular Release for Adhesive Capsulitis of the Shoulder

Abstract: BACKGROUND: This study was undertaken to evaluate the outcome of the arthroscopic capsular release for adhesive capsulitis of the shoulder.METHODS: This study retrospectively investigated thirty shoulders in 29 patients who presented with recalcitrant adhesive capsulitis and underwent arthroscopic treatments. Other than typical findings of adhesive capsulitis, combined pathologies in the glenohumeral joint and subacromial space were evaluated by arthroscopy. Clinical evaluations were performed using the Consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
4
6
0
Order By: Relevance
“…31.88 ± 7.52 at last follow up is coincident with other study that reported that after arthroscopic capsular release in managing shoulder adhesive capsulitis, there was an increase of 28.8 degrees of ROM in forward elevation, 5.3 degrees in external rotation, and 4.0 degrees vertebral levels in internal rotation. There was statistically significant increase in the Constant-score, Murley's forward elevation, and internal rotation but not in external rotation (20) . In other study, it was found that the mean Constant-score at 6 months postoperatively was 83.4 % of the values at the final follow-up.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…31.88 ± 7.52 at last follow up is coincident with other study that reported that after arthroscopic capsular release in managing shoulder adhesive capsulitis, there was an increase of 28.8 degrees of ROM in forward elevation, 5.3 degrees in external rotation, and 4.0 degrees vertebral levels in internal rotation. There was statistically significant increase in the Constant-score, Murley's forward elevation, and internal rotation but not in external rotation (20) . In other study, it was found that the mean Constant-score at 6 months postoperatively was 83.4 % of the values at the final follow-up.…”
Section: Discussionmentioning
confidence: 76%
“…As a result of arthroscopic capsular release, other studies have found that the overall results are favourable and comparable to those previously reported. After surgery, pain, functional scores of the shoulders and ranges of motion were significantly improved (20,(22)(23)(24)(25)(26)(27)(28)(29)(30) . There were a number of clinical parameters at 6 months post-operatively that were lower when compared to those at the final follow-up (31,32) .…”
Section: Discussionmentioning
confidence: 97%
“…Arthroscopic capsular release (ACR) and manipulation under anesthesia (MUA) are treatment options for primary frozen shoulder (FS). Both of these are useful for primary FS [ 1 - 3 ]. In addition, MUA is possible without the surgical equipment needed for an arthroscopic procedure.…”
mentioning
confidence: 99%
“…Although MUA is an useful option for primary FS, several complications such as proximal humerus fracture, shoulder dislocation, brachial plexus stretching injury, rotator cuff injury, and glenoid fracture may result [ 1 - 3 , 5 ]. Therefore, MUA should be performed with great caution.…”
mentioning
confidence: 99%
See 1 more Smart Citation